Field excursion as alternative teaching approach for civil engineering quantities and estimation course / Herda Balqis Ismail, Asmawati Che Hasan, Azinoor Azida Abu Bakar, Hawa Syamsina Md Supie, Siti Shahidah Sharipudin and Atiqah Najwa Zainuddin - Ismail, Herda Balqis; Che Hasan, Asmawati; Abu Bakar, Azinoor Azida; Md Supie, Hawa Syamsina; Sharipudin, Siti Shahidah; Zainuddin, Atiqah Najwa (UiTM Cawangan Johor, 2024)
This study explores the effectiveness of integrating experiential learning, specifically site visit, as part of a teaching method in the Civil Engineering Quantities and Estimation course. The course is crucial for developing the skills necessary for accurate project management and successful implementation of infrastructure projects. The research focuses on a group of year three of Diploma of Civil Engineering students at UiTM Johor Branch Pasir Gudang Campus in semester 20232 year of academic. The aim of this study is to compare students' performance in formative and summative assessments before and after participating in a site visit activity. The findings reveal that, while male students show modest {43.8%) improvement, female students demonstrate a significant {100.0%) improvement in their understanding of the course after the site visit. The results suggest that experiential learning, particularly site visits, can positively impact students' comprehension and performance in the Civil Engineering Quantities and Estimation course. The study recommends the incorporation of experiential learning methods into the curriculum, acknowledging the potential benefits for students' understanding and application of theoretical knowledge in real-world contexts